Rola i znaczenie rachunkowości w sytuacjach szczególnych w funkcjonowaniu przedsiębiorstw - Czerny, Janusz (Role and Meaning of Accounting of Enterprises in Particular Situations, 2005)
The enterprise milieu and internal reasons create factors which can limit its further development. Inhibition or limitation of developments makes a threat to continuation of enterprises activity. Therefore, as a result of miscellaneous factors, it comes to particular situations in functioning of enterprises which cause acceptance of a new hierarchy of purposes and strategy of operation. The purpose of its study is an attempt to present the role and meaning of information delivered by widely understood accounting for enterprises in particular situations, especially in the context of its usefulness in management.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 120-131